STORAGE MEDIA TECHNOLOGY USB FLASH DRIVE - Deni Wijaya Indra; Fivtatianti H, SKom, MM Fivtatianti H, SKom, MM (Jurnal Sistem Komputer, 2008)
USB Flash Drive is a type of NAND-type flash memory combined with a USB 1.1 or 2.0 and used as data storage devices smaller and lighter. Because of the sophistication that has made USB Flash Drive becoming increasingly popular as an alternative replacement disk that has been used to store data.Today USB Flash Drive measures less in length between 4-7 cm and a thickness of only 0.5 -1 cm. The user can put pocket pants or shirt. No wonder if now is a USB Flash Drive is not only popular among the IT course, Device this one was very, very popular until the elementary school level was already familiar with the USB Flash Drive as a storage medium.